Abundancia y distribución de nutrientes en la zona de la confluencia de la Corriente de Brasil y la Corriente de las Malvinas. Nutrientes preformados en las masas de agua de la región - Corrochano Fraile, Ana (Universidad de Barcelona, 2018)
Trabajo final presentado por Ana Corrochano Fraile para el Máster en Oceanografía y Gestión del Medio Marino de la Universitat de Barcelona (UB), realizado bajo la dirección de la Dra. Montserrat Vidal y del Dr. Carles Guallar de la Universitat de Barcelona (UB) y del Dr. Josep Lluís Pelegrí del Institut de Ciències del Mar (ICM-CSIC).-- 39 pages, 13 figures, 4 tables, 1 annex The region of confluence between Brazil and Malvinas (BMC) is one of the most important areas of the western South Atlantic. This is an energetic region of water just off the coast of Argentina where the warm poleward flowing Brazil Current (BC) and the cold equatorward flowing Malvinas Current (MC) converge causing variability in the physical characteristics and the organic/inorganic nutrients. The aim of this research was to determine preformed nutrients and its distribution in the water masses located at the BMC during March 2015.The Optimum Multi-Parameter analysis (OMP) was performed to obtain and classify the preformed nutrients in their corresponding water masses. In this study, the greatest concentrations of nitrate, phosphate and silicate were 44.5, 2.3 and 69.8 μM respectively, and located in deep MC influenced waters. For organic nutrients, DON (dissolved organic nitrogen) greatest concentrations were 15.2 -15.5 μM and DOP (dissolved organic phosphorous) concentrations were 0.95-1.1 μM located in deep water levels, and also in recent formation water masses such as AAIW1, AAIW2 (Antarctic Intermediate Water 1 and 2) and WSDW (Weddell Sea Deep Water). DOC (dissolved organic carbon) highest concentration (113 μM) was located in surface BC stations. The C:N:P ratio for organic nutrients suggests remineralisation of organic matter at BMC Este trabajo se ha llevado a cabo gracias a los proyectos: “Tipping corners in the Meridional overturning Circulation”, CTM2011-28867; y “Western boundary retroflections: connecting latitudinal transports and gyre recirculations in the Atlantic Ocean ”; CTM 2014-56987-P Peer Reviewed